2018 26th European Signal Processing Conference (EUSIPCO) 2018
DOI: 10.23919/eusipco.2018.8553615
|View full text |Cite
|
Sign up to set email alerts
|

Fast Hyperspectral Cube Reconstruction for a Double Disperser Imager

Abstract: We consider the problem of hyperspectral cube reconstruction with a new controllable imaging system. The reconstruction with a small number of images acquired with different configurations of the imager avoids a complete scanning of the hyperspectral cube. We focus here on a quadratic penalty reconstruction approach, which provides a fast resolution thanks to the high sparsity of the involved matrices. While such a regularization is known to smooth the restored images, we propose to exploit the system capabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
(11 reference statements)
0
9
0
Order By: Relevance
“…We follow the work of Ardi et al [16], who proposed a convex relaxation algorithm to recover the HS data cube. Although the DD CASSI is a snapshot imager, Ardi et al [16] suggested performing the cube recovery based on multiple acquisitions. This improves the reconstruction quality (see Section 5.2.2).…”
Section: Dd Cassi Matrix Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We follow the work of Ardi et al [16], who proposed a convex relaxation algorithm to recover the HS data cube. Although the DD CASSI is a snapshot imager, Ardi et al [16] suggested performing the cube recovery based on multiple acquisitions. This improves the reconstruction quality (see Section 5.2.2).…”
Section: Dd Cassi Matrix Modelmentioning
confidence: 99%
“…For this purpose, we perform an analysis based on "fast hyperspectral cube reconstruction" technology proposed by Ardi et al [16]. They exploit the DD CASSI and process the data with the Conjugate Gradient for Normal Equation (CGNE), a convex relaxation algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…To prevent smoothing across an edge, the components of the matrices Dx and Dy corresponding to an edge pixel are set to zero [25]. The edges are detected on the panchromatic image using a state-of-the-art edge finding procedure.…”
Section: Reconstruction Of the Hyperspectral Datacube Via Edge Presermentioning
confidence: 99%
“…The used reconstruction algorithm is based on an edgepreserving regularization which smoothes spectral-spatial features, which obliges nearby pixels to have similar spectra but avoids smoothing of sharp spatial features, therefore preventing mixing of the spectra between distinct regions [25]. This regularization is related to edge-preserving regularization [26] and to the well-known Total Variation [27] regularization which aims to preserve the unknown edges, while smoothing the images to regularize the solution.…”
Section: Introductionmentioning
confidence: 99%
“…Classification of multiple spectra is possible with only a few acquisitions as shown in [18,19], using a scheme where the DMD mask adapts for each new acquisition to improve classification accuracy. Furthermore, there is potential to use regularization approaches to exploit homogeneity within the hyperspectral datacube, allowing full cube reconstruction with only a handful of acquisitions [20]. The easy access to the panchromatic image allows an adaptive approach to datacube acquisition, whereby one exploits features from the panchromatic image to optimize the DMD mask for a particular acquisition scheme, or even change the acquisition scheme itself.…”
Section: Introductionmentioning
confidence: 99%